Supraspinous ligament arc tangent guided freehand thoracic pedicle screw insertion technique: high parallelism between screws and upper endplate - Peng, Fushuai; Gao, Meng; Li, Qiang; Jiang, Zhensong; Chen, Fei; Sun, Mingtong; Lai, Yudong; Wang, Haoyu; Wang, Xingpeng; Li, Tao; Zhang, Wen (Frontiers in Surgery, 2023)
Research objective: To propose a technique for placing pedicle screws in the thoracic spine using the Supraspinous ligament Arc Tangent (SLAT) as a guide to increase the safety and stability of screw placement. Content and methods: A retrospective analysis of postoperative anteroposterior and lateral X-ray images was performed for 118 patients with thoracic spine diseases who received conventional freehand technique from January 2016 to May 2020 and SLAT-guided technique since June 2020 to present. The diagnoses included thoracic spinal stenosis, deformity, fractures, infections, and tumors. The angle between the screw and the upper endplate was categorized as grade 1 (0°-5°), grade 2 (5°-10°), and grade 3 (>10°). Three surgeons with more than 10 years of experience in spinal surgery measured the angle between the screw and the upper endplate in the lateral view. Chi-square test was used for statistical analysis, and p<0.05 was considered statistically significant. Results: A total of 1315 pedicle screws were placed from T1 to T12 in all patients. In the conventional freehand technique group, 549 screws were grade 1, 35 screws were grade 2, and 23 screws were grade 3. In the SLAT-guided freehand technique group, 685 screws were grade 1, 15 screws were grade 2, and 8 screws were grade 3. The data of each group was P<0.05 by Chi-squared test, which was statistically significant, indicating that the SLAT-guided freehand technique resulted in a higher rate of parallelism between the screws and the upper endplate. All patients underwent intraoperative neurophysiological monitoring, immediate postoperative neurological examination, postoperative X-ray examination, and assess the eventual recovery. The screws were safe and stable, and no complications related to pedicle screw placement were found. Conclusion: The SLAT-guided freehand technique for placing pedicle screws in the thoracic spine can achieve a higher rate of screw-upper endplate parallelism, making screw placement safer and more accurate. Our method provides a convenient and reliable technique for most spinal surgeons, allowing for increased accuracy and safety with less fluoroscopic guidance. Keywords: freehand technique, Supraspinous ligament Arc Tangent, thoracic pedicle, screws, parallelism.